Characteristics of External Respiratory System Parameters in School-Age Children under the Environmental Conditions of the Republic of Karakalpakstan - Sevaraxon, Masharipova (Indonesian Journal Publisher, 2025)
This study is aimed at assessing the indicators of the external respiratory system in school-aged children living under the environmental conditions of the Republic of Karakalpakstan. A cross-sectional observational study was conducted involving 300 children aged 7 to 14, using spirometry to measure lung vital capacity (VLC) and peak expiratory flow rate (PEFR), pulse oximetry to assess blood oxygen saturation (SpO₂), and structured questionnaires to collect data on environmental and behavioral factors. The results showed that around 60% of the participants had reduced VLC and PEFR, and the average SpO₂ was 95%, indicating early signs of respiratory dysfunction. Environmental factors, such as high levels of dust and agrochemical use, were significantly correlated with reduced respiratory function. Furthermore, climatic conditions like low humidity and temperature fluctuations exacerbated these effects. Social and behavioral factors, including low physical activity and poor nutrition, were also linked to respiratory impairment. Comparative analysis with other Central Asian regions revealed a 15–20% higher prevalence of respiratory disorders among Karakalpak children. The findings highlight the urgent need for preventive interventions, including enhanced air quality monitoring, promotion of physical activity, improved nutrition, and regular medical screenings. These measures are essential to reduce the risk of chronic respiratory diseases and improve long-term health outcomes for children in environmentally vulnerable areas.